The Role of Rice Production as a Key Factor in Enhancing Cambodian Agriculture: A Systematic Review - Srun Puthearith; Mardy Serey (PT PUSTAKA CENDEKIA PUBLISHER, 2024)
Rice production is central to Cambodia’s agriculture, contributing to economic development, poverty alleviation, food security, and sustainable farming practices. This systematic review aims to analyze the multifaceted role of rice production in enhancing Cambodian agriculture. The review draws on studies related to agricultural productivity, economic impacts, rural development, and government policy frameworks, providing an integrated perspective on how rice production drives Cambodia's agricultural progress. By understanding the multifaceted role of rice cultivation, policymakers and stakeholders can develop effective strategies to further promote agricultural progress and improve the livelihoods of Cambodian farmers.